2010
DOI: 10.1590/s0102-09352010000400038
|View full text |Cite
|
Sign up to set email alerts
|

Ultrassonografia e histopatologia renal em cães

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
3
0
1
Order By: Relevance
“…This fact has been observed in studies on the correlation of sonographic and histopathological findings in renal diseases 45 .…”
Section: Resultssupporting
confidence: 53%
“…This fact has been observed in studies on the correlation of sonographic and histopathological findings in renal diseases 45 .…”
Section: Resultssupporting
confidence: 53%
“…Burti et al (2020) demonstrated that the number and severity of ultrasound changes are correlated with the severity of kidney degeneration lesions on histopathological examination. Therefore, even if the specific diagnosis is not achieved by the method, it brings enough information to guide future procedures (Carvalho et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The literature considers that in cases of AKI, hyp-erechogenicity is due to the presence of inflammatory infiltrate, proteins, cylinders, and calcium and is directly related to the presence of interstitial changes and loss of renal function (Pennick and D'Anjou, 2015;Garreballah et al, 2015). The correlation between cortical hyperechogenicity, histological abnormalities, and increase in serum creatinine suggests that high-risk patients may have kidney damage (Araujo et al, 2010;Carvalho et al, 2010;Bragato et al, 2017). Therefore, due to its high prevalence, cortical hyperechogenicity may represent a sentinel sign of renal dysfunction also in those animals with mean serum creatinine values below 1.6 mg / dl if they have risk factors for the development of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tais características também foram utilizadas por Carvalho et al (2010), que comparam os resultados dos achados ultrassonográficos com a histologia de tecidos renais. Dos 26 cães estudados, 11 apresentaram algum tipo de alteração no exame ultrassonográfico que compreenderam alterações de ecogenicidade, alterações no tamanho renal, alterações na relação entre as regiões cortical e medular, alteração de contorno e na ecotextura dos tecidos renais.…”
Section: Discussionunclassified